2004
DOI: 10.1002/mc.20039
|View full text |Cite
|
Sign up to set email alerts
|

Proto oncogene/eukaryotic translation initiation factor (eIF) 4E attenuates mevalonate‐mediated regulation of 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase synthesis

Abstract: The rate-limiting enzyme for mevalonate synthesis in mammalian cells is 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. Products of mevalonate synthesis are required for cell cycle progression as well as cell growth and survival. In tumor cells, HMG-CoA reductase is generally elevated because of attenuated sterol-mediated regulation of transcription. However, tumor cell HMG-CoA reductase remains sensitive to post-transcriptional regulation by mevalonate-derived isoprenoid intermediates of cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 85 publications
(218 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that rapamycin at 10 nM at 4 h, a clinically relevant concentration (Ref. 97), is capable of inhibiting the mTORC1 pathway, thus impeding cellular proliferation, growth and translation initiation (Refs 98, 99). Analogues of rapamycin (‘rapalogues’) have been approved for use in several forms of metastatic cancers and continue to be evaluated in Phase III solid tumour studies.…”
Section: Rapamycin and Mtor Inhibitionmentioning
confidence: 99%
“…It has been shown that rapamycin at 10 nM at 4 h, a clinically relevant concentration (Ref. 97), is capable of inhibiting the mTORC1 pathway, thus impeding cellular proliferation, growth and translation initiation (Refs 98, 99). Analogues of rapamycin (‘rapalogues’) have been approved for use in several forms of metastatic cancers and continue to be evaluated in Phase III solid tumour studies.…”
Section: Rapamycin and Mtor Inhibitionmentioning
confidence: 99%
“…The mevalonate pathway produces isoprenoids that are vital for diverse cellular functions, ranging from cholesterol synthesis to growth control. Several mechanisms for the feedback regulation of low-density-lipoprotein receptors and of two enzymes involved in mevalonate biosynthesis ensure the production of sufficient mevalonate for several end products [ 5 ]. Manipulation of this regulatory system could be useful in treating certain forms of cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%